Getting inside the mind of leaders and advisers: a data collection strategy for historical case studies in IR - He, Wendy (2024)
In the last few decades, a new wave of behavioral research has become prominent in International Relations (IR) and led to a welcome expansion of laboratory experiments as well as stimulating dialogues with neurosciences, biology, and genetics. Simultaneously, the study of leaders and their advisers has made a significant comeback. However, in the qualitative study of real-world foreign policy decisions, little progress has been made to provide IR researchers with a strategy to collect data on the mental processes of leaders and advisers. In this paper we introduce the Critical Decision Method (CDM) and adapt it to historical case studies research in IR. We show how the CDM makes the data collection on cognition more systematic and replicable by providing an 11-item checklist to guide observations on how the human mind works in crisis situations. We argue that this data collection strategy helps bring together insights which shed new light on President Truman’s decision to intervene in the Korean War. Contrary to the conventional wisdom that fast foreign policy decisions tend to be flawed, Truman’s quick decision was well adapted to the circumstances.